Perioperative serum cortisol levels in ACTH sufficient and ACTH deficient patients during transsphenoidal surgery of pituitary adenoma - Borg, Henrik (Endocrine, 2018)
PURPOSE: No previous study has analyzed serum cortisol levels during transsphenoidal endoscopic pituitary surgery in patients with and without hydrocortisone (HC) substitution. METHODS: A total of 15 patients undergoing surgery for a pituitary adenoma were studied. Those with normal ACTH function were either not given HC (n = 7) or received 50 mg intravenous HC at the start of surgery (n = 4). Patients with ACTH deficiency received intravenous HC of 100 mg in the morning before surgery (n = 4) with the additional 50 mg for an afternoon operation (n = 2). Propofol and remifentanil were used as anesthetics. Serum cortisol was measured at the start of and every 30 min during surgery. RESULTS: Among 7 patients with normal ACTH function without HC substitution, cortisol levels before surgery were 126–244 nmol/L, among the 4 patients undergoing surgery in the morning, whereas the 3 who underwent surgery in the afternoon had lower levels, 38–76 nmol/L. During nose/sinus surgery cortisol levels decreased to 79–139 and 24–54 nmol/L, respectively. At intrasellar manipulation a distinct rise was noted. Also, in the 4 ACTH sufficient patients receiving HC, cortisol levels decreased during nose/sinus surgery, but only with a slight increase during intrasellar surgery. In the 4 ACTH deficient patients cortisol peaked at 1914–2582 nmol/L. CONCLUSIONS: Patients with normal ACTH function without HC substitution had very low cortisol levels during the first part of surgery, likely suppressed by the anesthetics. After mechanical impact in the sella, a marked increase in cortisol was noted. Supraphysiological cortisol levels were achieved with our routine HC substitution, advising us to reduce the supplementation.